The Influence of Blended Learning Model Based on Problems of Physical Learning Achievements by Students of Class X Science in SMA 6 Denpasar Academic Year 2017/2018 - Utami, Ni Putu Nadia Nikki; Santyasa, I Wayan; Suswandi, Iwan (Universitas Ahmad Dahlan, 2018)
Learning achievement is the result achieved by someone after doing the learning process. One of the factors that influence learning achievement is the use of the learning model. This study aims to know the differences in achievement of students learning to use problem-based blended learningmodels and traditional blendedlearning. This study uses a quasi-experimental method of